Answer:
The correct answer is in bold below written in two different ways. I think that the two middle options of your problem were given by mistake. The correct answer is not in the options.
Explanation:
cost of yogurt = cost of toppings + cost of yogurt with 1 topping
cost of yogurt with 1 topping = $3.65
cost of yogurt = cost of toppings + 3.65
cost of 1 additional topping = $0.45 * 1
cost of 2 additional toppings = $0.45 * 2
cost of x additional toppings = $0.45 * x = 0.45x
Since 1 topping is included in the $3.65 charge, if you pay for x additional toppings, you will have x + 1 total number of toppings. That means you must pay for only x - 1 additional toppings to have a total of x toppings.
One topping is already included in the $3.65 charge, so you pay for only x - 1 additional toppings.
cost of x - 1 additional toppings = 0.45(x - 1)
cost of yogurt = 0.45(x - 1) + 3.65
y = 0.45(x - 1) + 3.65
y = 0.45x - 0.45 + 3.65
y = 0.45x + 3.2